NARRATIVE INQUIRY : AN APPEALING SELF-REFLECTION `ON A PRE-SERVICE TEACHER IN VIDEO-MEDIATED TEACHING PRACTICA - Vindia Alif Nur Fingky (Faculty of Teaching and Education, University of August 17, 1945, Banyuwangi, 2021)
Narrative inquiry : an appealing self-reflection on a pre-service teacher in video-mediated teachingpractica. Experience is the beginning of learning about life, perfectly the different of teaching education in another country. however, with the experience can appreciate directly what happened and how it appends. This study discussed and analyzed about the experience and understanding about language, method, culture and the habit of the student in Thailand English education school. Students This Research aimed to improve the pre-service teacher skill in English lesson in International Teaching Practicum Program. This research was conducted by using Self-Reflection on Narrtive Inquiry as a Learning experience. The subject of this research is researcher as a pre-service teacher. The objective of this research was to improve the pre-service teacher skill in English lesson by using Self-Reflection on Narrative Inquiry as a Learning Experience at Darul Ulom Nibongbaru School in Thailand. The researcher conducted autobiographical writing to research about the experience and using the other data collection as an interview, photovoice and reflecting journal to support this research. The researcher as a pre-service teacher through a narrative inquiry can found the pragmatic approach to support international teaching practicum. In this study can help both teacher and student reflect on, question and learn the understanding of pre-service teacher in international teaching practicum program in Thailand from their storied experience. The data gathered trought narrative autobiography, interviews, reflecting journaling, photo voice and video recording as a mediated.